Trying the Unemployed: Justification and Critique, Emancipation and Coercion Towards the `Active Society' - Magnus Paulsen Hansen (Copenhagen Business School (CBS), 2017)
Since the late 1980s, European welfare states and labour market regulation have gradually but radically been transformed into ways of underpinning a more “active society” where active usually entails paid work or activities, such as training and qualification, that aim towards work. The thesis investigates the transformation towards the `active society' through the spectre of unemployment and how it is governed. Two puzzles in the transformations have motivated the inquiry: firstly, the co-existence of a plurality of different, and often contradictory, conceptions of who the unemployed are and why they are unemployed; and secondly, the co-existence of wills to emancipate the unemployed alongside the justification of using coercive measures towards them. This thesis argues that if we want to understand the varieties within the transformations, the “what?” question, it is necessary to address the “how?”; i.e., how transformations are legitimised. Here, ideas and morality are pivotal. Inspired by French pragmatic sociology (Boltanski and Thévenot), the ideas are approached as cities of unemployment that are mobilised to justify and criticise policies related to the governing of unemployment. In these situations where the question of what is the best way to govern unemployment is put to the test, cities of unemployment enable actors to prepare and qualify the reality of the situation for critique and justification. Each city of unemployment is founded on a principle with specific principles to try or test both those who govern and the subjects inhabiting each city, thus entailing a specific understanding of what emancipating the unemployed involves, i.e., what kind of moral subject the unemployed person is with what kind of needs and characteristics. The thesis thus asks which cities of unemployment are mobilised in contemporary reform processes of the governing of unemployment, how are the cities mobilised to justify and criticise, and how do the cities sediment into instruments and institutions governing the unemployed?
hdl:10398/9465
Keywords: 650